Gender differences in the interrelationships of Chinese student’s personality traits of the «Big five» and the «Dark triad» - Nie, Xinchun; Fourmanov, Igor A. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
Gender differences in the interrelationships of the personality traits of the «Big five» and the «Dark triad» among Chinese students are considered. As a result, a comparative analysis showed that Chinese women compared with men had statistically higher rates of agreeableness and open-Mindedness, and Chinese men compared with women had statistically higher rates of psychopathy. There were no significant differences in the indicators of extroversion, conscientiousness, negative emotionality, narcissism and Machiavellianism. Correlation analysis allowed us to establish both differences and similarities in the interrelationships of the features of the «Big five» and the «Dark triad». It is established that regardless of the gender of Chinese students, agreeableness with Machiavellianism and psychopathy, and conscientiousness with psychopathy are negative emotionality.